2010
DOI: 10.1021/ic902595c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Iron Sequestration Equilibria of Novel Exocyclic 3-Hydroxy-2-pyridinone Donor Group Siderophore Mimics

Abstract: The synthesis of a novel class of exocyclic bis- and tris-3,2-hydroxypyridinone (HOPO) chelators built on N2 and N3 aza-macrocyclic scaffolds and the thermodynamic solution characterization of their complexes with Fe(III) are described. The chelators for this study were prepared by reaction of either piperazine or N, N’, N”-1,4,7-triazacyclononane with a novel electrophilic HOPO iminium salt in good yields. Subsequent removal of the benzyl protecting groups using hydrogenolysis gave bis-HOPO chelators N2(etLH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 56 publications
(149 reference statements)
2
18
0
Order By: Relevance
“…The pFe values are 23.12, 26.44, and 23.23 for Fe–ICL670, Fe– 5a , and Fe– 5b , respectively. The ICL670 pFe value determined in this study is close to the one reported in the literature (pFe =23.5), [29] which validates our calculation procedure for water-insoluble systems. The pFe values determined in this study for ICL670-based calix[4]arene ligands (pFe >20) met the criteria for application as iron chelation therapy agents.…”
Section: Resultssupporting
confidence: 88%
“…The pFe values are 23.12, 26.44, and 23.23 for Fe–ICL670, Fe– 5a , and Fe– 5b , respectively. The ICL670 pFe value determined in this study is close to the one reported in the literature (pFe =23.5), [29] which validates our calculation procedure for water-insoluble systems. The pFe values determined in this study for ICL670-based calix[4]arene ligands (pFe >20) met the criteria for application as iron chelation therapy agents.…”
Section: Resultssupporting
confidence: 88%
“…Very few polyaza macrocycles bearing HOPO coordinating groups have been described [48,[51][52][53][54]. Macrocycles offer the potential to fine tune the metal chelating properties by varying the cycle's size and fexibility.…”
Section: Introductionmentioning
confidence: 99%
“…A proportional decrease was observed for the absorbance at 220 and 270 nm for gallic acid (GA) and at 240 and 300 nm for salicylic acid (SA). The two isosbestic points (IUPAC 2007) confirmed the formation of the metal-organo complexes and are indicative of a transition between two light absorbing species in all recorded spectra (Harrington et al 2010).…”
Section: Ultraviolet Spectrophotometric Determination Of Aluminum-orgmentioning
confidence: 55%